2016
DOI: 10.14295/oh.v22i1.855
|View full text |Cite
|
Sign up to set email alerts
|

Influência de ácido indolbutírico no enraizamento de estacas semilenhosas de Campomanesia aurea

Abstract: Influence of indolebutyric acid in the rooting of Campomanesia aurea semihardwood cuttings 94Ornamental Horticulture CAMPINAS-SP | V. ABSTRACT Campomanesia aurea (O. Berg) is a species native to southern Brazil, naturally occurring from the state of São Paulo to Rio Grande do Sul, and presenting a great ornamental potential. The objective was to verify the rooting of semihardwood cuttings of Campomanesia aurea using indolebutyric acid (IBA) doses. The cuttings were collected in the municipality of Barão do Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
3
5
1
Order By: Relevance
“…Similarly as observed in this study, the use of IBA did not affect the rooting of Jasminum polyanthum (SILVA et al, 2012), Drimys brasiliensis (ZEM et al, 2015), Campomanesia aurea O. Berg (EMER et al, 2016) and Varronia curassavica Jacq (BISCHOFF et al, 2017).…”
Section: Resultssupporting
confidence: 81%
“…Similarly as observed in this study, the use of IBA did not affect the rooting of Jasminum polyanthum (SILVA et al, 2012), Drimys brasiliensis (ZEM et al, 2015), Campomanesia aurea O. Berg (EMER et al, 2016) and Varronia curassavica Jacq (BISCHOFF et al, 2017).…”
Section: Resultssupporting
confidence: 81%
“…High temperatures promote a faster sprout growth and a greater rooting (Hartmann et al, 2011). The results of rooting obtained in this study were higher than those found in previous experiments for cuttings of C. aurea collected directly from the field: 28, 20, 8 and 25%, in the summer, autumn, winter and spring, respectively (Emer et al, 2016;Emer et al, 2018). Among the factors that may have contributed to the results obtained by minicutting, there are better nutrition of matrix plants and the juvenile state of the propagules.…”
Section: Rooting Of Cuttingscontrasting
confidence: 81%
“…Previous research has shown that cuttings of C. aurea collected directly from the field present a low rooting (Emer et al, 2016;Emer et al, 2018). Therefore, the production of seedlings by cuttings collected from minigardens might be an alternative for the vegetative propagation of this species, since there is a control of nutritional management in matrix plants, besides obtaining juvenile material, which is more suitable to rooting.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, it did not present differences for the different concentrations of IBA, but it is important to emphasize that the regulators can also influence the quality of the root system (FACHINELLO et al, 2005), which will have a direct relation with seedling development, as well as with their survival at transplant (LIMA and OHASHI, 2016), consequently presenting faster and more vigorous growth (REIS et al, 2000). Similar results were obtained in the rooting of Campomanesia aurea O. Berg cuttings, where IBA also had no influence on root system quality (EMER et al, 2016). Moreover, in cuttings of Mikania micrantha Kunth (FERRIANI et al, 2007) and Jasminum mesnyi Hanceos (ALTHAUS et al, 2007), the authors found that the use of synthetic auxin increased the length of the roots formed, influencing their quality.…”
Section: Resultsmentioning
confidence: 54%